Ḥammam al-Ṣafi: an ayyubid bath in Damascus - Daiber, Verena (Zeitschrift für Orient-Archäologie, 2010)
The Ḥammam al-Ṣafi in Damascus was long believed to have vanished and was only recently rediscovered. The classical medieval layout of this bathhouse was only slightly modified during the centuries. Remarkable is the elaborate design of the wasṭānī that still testifies to the outstanding prominence of this central part of the structure.